Determinasi Literasi Digital, Pemanfaatan AI, dan Minat Belajar Dalam Meningkatkan Digital Responsibility Mahasiswa Pendidikan Administrasi Perkantoran - Wulandari, Wahyuning Trisnani Ayu; Wulandari, Siti Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of digital literacy, Artificial Intelligence (AI) utilization, and learning interest on the digital responsibility of students in the Office Administration Education Study Program at Universitas Negeri Surabaya. The scope of this research focuses on how cognitive, technological, and affective factors contribute to responsible digital behavior among university students in the era of artificial intelligence.This research employed a quantitative explanatory approach to examine causal relationships among variables. The population consisted of 639 students from the 2023 and 2024 cohorts, with a sample of 246 respondents selected using proportional random sampling based on the Slovin formula. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics and multiple linear regression with the assistance of SPSS software. Prior to regression analysis, classical assumption tests including normality, multicollinearity, and heteroscedasticity tests were conducted. The results indicate that AI utilization and learning interest have a significant positive effect on students’ digital responsibility, while digital literacy does not show a significant partial effect. Simultaneously, digital literacy, AI utilization, and learning interest significantly influence digital responsibility. The coefficient of determination shows that these variables explain 46.9% of the variation in digital responsibility, while the remaining 53.1% is influenced by other factors outside the model.In conclusion, AI utilization and learning interest play an important role in strengthening students’ digital responsibility. Therefore, integrating ethical AI use and fostering learning interest in higher education can support the development of responsible digital behavior among students